A study of search engines and its influence on youth information skimming behaviours. (9th October 2020) - Bhandari, Ravneet Singh; Sharma, Himani
The individuals today are highly dependent on internet which is built on data and access to relevant data perhaps lead to various advantages. The human hunger for information has prompted the development of online 'search engines' over recent time and are most broadly utilised instruments in the contemporary world. This research paper focuses on the various elements of search engines on information skimming behaviour of young users. The results obtained indicated that elements associated to search engines i.e., relevant results obtained on the result page, comprehensive structure, free access and latest updates available on search engines in terms of data positively affects the information skimming behaviour of users. The information was accumulated through structured questionnaire from 313 respondents which were chosen by random sampling technique from the National Capital Region (NCR) of India. The information gathered from the respondents was loaded on SAS university edition for statistical analysis.